Design and Synthesis of Hydrazone‐Bearing Benzenesulfonamides as Carbonic Anhydrase VB Inhibitors. Issue 47 (14th December 2021) - Urbelytė, Liucija; Bagdonas, Martynas; Grybaitė, Birutė; Vaickelionienė, Rita; Mickevičiūtė, Aurelija; Michailovienė, Vilma; Matulis, Daumantas; Mickevičius, Vytautas; Zubrienė, Asta
Abstract: The α‐amino acid derivatives are constituents of many bioactive compounds and display a wide variety of biological activities. We have synthesized a series of new benzenesulfonamide derivatives bearing α‐amino acid moiety at para ‐position and evaluated their binding affinity to human carbonic anhydrase isozymes by fluorescent thermal shift assay. The dichloro‐ and monobromo‐substitutions on the benzenesulfonamide ring have been introduced to determine the halogenation effect on the binding affinity. Chloro substituents at 3, 5‐positions of benzenesulfonamide derivatives increased the affinity for all carbonic anhydrases as compared to non‐chlorinated compounds. The hydrazone‐bearing 3, 5‐dichlorobenzenesulfonamides 9 a, 9 d, and 12 exhibited a low nanomolar affinity for CA VB ( Kd in the range of 6.6–8.1 nM), an isozyme implicated in diseases of the central nervous system and obesity. Abstract : Novel potential antiobesity compounds: New α‐amino acid derivatives with hydrazone, thiosemicarbazide and azole moieties were synthesized and tested for binding affinity to twelve carbonic anhydrase isozymes. Several compounds exhibited nanomolar dissociation constants for mitochondrial enzyme CA VB, which is recognised as potential target for designing antiobesity agents.